Synthesis of graphene-templated inorganic nanoparticles - Yuan, Xintong. (2011)
Graphene has triggered numerous attentions in both nanoscience and nanotechnology nowadays owing to its peculiar atomic structure and the fascinating properties. Fabrication of nanoparticles with controllable morphologies and novel properties is also emerging as a significant field. In this report, we attempt to synthesize inorganic nanoparticles by using graphene as templates. Typically, syntheses of gold nanoparticles and Fe3O4 nanoparticles will be involved. After suitable modification of the surface with PFVSO3, gold nanoparticles could be successfully deposited on the surface of graphene in a facile reduction of HAuCl4 at 60 °C by the functionalized rGO. The evolution of growth will be monitored by changing the incubation time. After characterized with UV-Vis spectroscopy and Transmission Electron Microscopy, special arrow-like gold nanoparticles were discovered when incubation time is over 2days. Fe3O4 nanoparticles were produced by a simple coprecipitation process by using graphene oxide as templates. The effects of temperature and reaction time are investigated and explicated by TEM images. Lastly, the growth mechanism of both graphene-templated gold and Fe3O4 nanoparticles will be proposed based on the experiment observations.